Southerned: queer marginality in two souths - Scott, Jessica A (School of African and GenderStuds, Anth and Ling, 2019)
The metropolis has featured prominently in queer theory, cultural productions and advocacy work as the ideal site of queer life (Massad, 2002; Gray, 2009; Herring, 2010). Because of the concentration of resources in the metropole and discursive investments in locating ‘outof-the-way places’ (Tsing, 1993) at a temporal and geographic distance from metropolitan centres, I argue that queer organising in ‘out-of-the-way places’ is ‘southerned’. In other words, work that happens at the geographic margins continues to be rendered unrecognisable in a metric of ‘rights’, generated in a specific location and projected as ‘universal’. This dissertation is an account of the way that ‘discursive formations’ (Foucault 1972) shape the context for queer presence and work in ‘out-of-the-way places.’ The ethnographic work presented here was conducted in the United States South and South Africa over a period of two years, during which I collected and analysed public presentations and semi-structured in-depth interviews thematically and with discourse analysis. Through field work in two ‘souths’, the analysis presented here is situated in relation to a body of theoretical work that is interested in spatial and temporal politics of sexuality that frame ‘out-of-the-way places’ as inhospitable to queer existence. The hegemonic discourses of ‘rights’ generated in the metropole renders the kinds of work and existence carried out by queer bodies in ‘out-of-the-way places’ illegible. Queer work is ongoing in ‘out-of-the-way places’. This dissertation seeks to understand how that work is shaped both by the contexts in which the work unfolds and by the metronormative demands placed on what working queerly is supposed to look like. The research concludes that the complexities of queer existence and queer work in the ‘two souths’ represented here must be understood on their own terms rather than through the reductive lens of expectations and interpretations projected from the metropole. In order for queer work to thrive in ‘out-of-the-way places’, historical and contemporary issues that are residues of colonial legacies of resource extraction, violence, exploitation, environmental degradation and restricted access to a range of things not reducible to the metronormative rubric of ‘rights’ must be addressed.